Hydrometeorological conditions drive long-term changes in the spatial distribution of Potamogeton crispus in a subtropical lake - Yang, Ke; Yin, Yi; Xu, Ying; Wang, Shaobo; Gao, Mingyuan; Peng, Kai; Luo, Juhua; Gao, Junfeng; Cai, Yongjiu (Frontiers in Plant Science, 2024)
Globally, anthropogenic disturbance and climate change caused a rapid decline of submerged macrophytes in lake ecosystems. Potamogeton crispus (P. crispus), a species that germinates in winter, explosively expanded throughout many Chinese lakes, yet the underlying mechanism remained unclear. Here, this study examined the longterm changes in the distribution patterns of P. crispus in Lake Gaoyou by combining remote sensing images and hydrometeorological data from 1984 to 2022, and water quality data from 2009 to 2022. It aims to unravel the relationships between the distribution patterns of P. crispus and hydrometeorological as well as water quality factors. The results showed that the area of P. crispus in Lake Gaoyou showed a slight increase from 1984 to 2009, a marked increase from 2010 to 2019, followed by a decline after 2020. Spatially, P. crispus was primarily distributed in the western and northern parts of Lake Gaoyou, with less distribution in the central and southeastern parts of the lake. Wind speed (WS), temperature (Temp), water level (WL), ammonia nitrogen (NH3-N), and Secchi depth (SD) were identified as the key factors regulating the variation in P. crispus area in Lake Gaoyou. We found the P. crispus area showed an increasing trend with increasing Temp、WL and SD and decreasing WS、NH3-N.The influence of environmental factors on the area of P. crispus in Lake Gaoyou varied among seasons. The results indicated that hydrometeorology (WS, Temp, WL) may override water quality (NH3-N, SD) in driving succession of P. crispus distribution. The findings of this study offer valuable insights into the recent widespread expansion of P. crispus in shallow lakes across Eastern China.